2010
DOI: 10.1371/journal.pone.0013635
|View full text |Cite
|
Sign up to set email alerts
|

Immunocontraception in Wild Horses (Equus caballus) Extends Reproductive Cycling Beyond the Normal Breeding Season

Abstract: BackgroundAlthough the physiological effects of immunocontraceptive treatment with porcine zona pellucida (PZP) have been well studied, little is known about PZP's effects on the scheduling of reproductive cycling. Recent behavioral research has suggested that recipients of PZP extend the receptive breeding period into what is normally the non-breeding season.Methodology/Principal FindingsTo determine if this is the case, we compiled foaling data from wild horses (Equus caballus) living on Shackleford Banks, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 55 publications
(115 reference statements)
2
32
1
Order By: Relevance
“…The protracted breeding season of PZP-vaccinated females found in our study, as well as by Nuñez et al [38], indicates that horses that would normally conceive during their first or second reproductive cycle of the year continue to cycle throughout the year and then only conceive when contraception sufficiently decays. This inherently extends the breeding season and challenges the physiological constraints assumed to be regulating fertility.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The protracted breeding season of PZP-vaccinated females found in our study, as well as by Nuñez et al [38], indicates that horses that would normally conceive during their first or second reproductive cycle of the year continue to cycle throughout the year and then only conceive when contraception sufficiently decays. This inherently extends the breeding season and challenges the physiological constraints assumed to be regulating fertility.…”
Section: Discussionsupporting
confidence: 81%
“…This indicates surprising plasticity in birth phenology of temperate latitude horses given the physiological mechanisms thought to be driving reproductive cyclicity. At Shackleford Banks, North Carolina, USA, female feral horses exhibited estrus beyond the normal breeding season after being vaccinated annually with PZP for 1–6 years [38]. Based on the observed birth phenology in our study, this phenomenon occurred in our subjects as well; however, we recorded 81.4% of 328 documented births between March 1 and June 21.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Possible negative effects of ZP vaccines include speciesspecific ovarian pathology and multiple infertile oestrous cycles (in polyoestrous species), leading to extended breeding season, increased movements, potential late births and disruption of social hierarchy Curtis et al 2007;Kirkpatrick et al 2009Kirkpatrick et al , 2011Nuñez et al 2009Nuñez et al , 2010. Other studies on white-tailed deer and feral horses have reported that treatment with ZP vaccines does not affect time budget, social behaviour and body condition (Miller et al 2001;Hernandez et al 2006;Ransom et al 2010).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%
“…As a result, females lose body condition, which in turn decreases offspring survival and female fertility (Nuñez et al 2010). Puberty may be delayed and, in severe circumstances, female reproductive cyclic activity may cease, and increased adult mortality may occur (Gaillard et al 2000a).…”
Section: Introductionmentioning
confidence: 99%